Sternotomic resection of an anterior mediastinal cystic teratoma with pericardial fistula - I, Lomangino; PP, Gelera; G, Maffeis; E, Addamo; F, Rosati; S, Alfonso; MR, Benvenuti (Global Journal of Medical and Clinical Case Reports, 2024)
Background: Mediastinal teratomas are rare tumors and the majority of them are mature teratomas, benign lesions characterized by slow growth and low malignant potential. Signs and symptoms are infrequent; hence the diagnosis is often incidental. Complicated cases are rare and are traditionally treated with elective surgery. Our case report presents a patient with a teratoma complicated by pericardial fistulization requiring emergency surgery: the only case described in the literature. Case presentation: A 36-year-old male with no relevant medical history reported acute thoracic pain. Chest CT scan shows a mediastinal mass (compatible with cystic teratoma) compressing the superior vena cava, the heart, and pericardial involvement. The patient was first subjected to pericardiocentesis and then an en-bloc resection of the mediastinal lesion was performed via sternotomy. Discussion and conclusion: Mediastinal lesions require an accurate differential diagnosis, despite the diagnosis often being incidental in the absence of clinical symptoms. Conversely, if symptomatic, complicated cases can lead to life-threatening situations, where the exeresis of such lesions might require urgent, complex, and multidisciplinary surgical intervention.